Sp-nitrogen and γ-ray modulating multiply γ-graphyne for anchoring Pt nanoparticles to boost oxygen reduction activity and stability. (December 2022) - Wang, Wei; Yao, Fengting; Zeng, Ming; Pei, Mengfan; Min, Chunying; Xu, Zhiwei; Shao, Ruiqi; Liu, Shengkai; Shi, Haiting; Xia, Yuanhua
Highlights: The co-regulation of sp-N doping and γ-ray irradiation over γ-graphyne. Sp-N induced more partial positive charge, regulated the electron density. γ-Ray irradiation regulates the defect structure of γ-graphyne. The superior activity and stability of Pt/N50 -GY from synergistic effect. Abstract: γ-Graphyne (GY) is a potential carbon support for anchoring platinum nanoparticles (Pt NPs) in oxygen reduction reaction (ORR). However, the high oxygen penetration barrier of primitive GY intercepts its application for ORR. Herein, based on the stronger negative charge density of sp-hybridized nitrogen (sp-N) atoms and the regulation of γ-ray irradiation on carbon nanostructure, a Pt/N50 -GY catalyst with a multi-level pore structure, larger specific surface area (twice that of original GY) and more Pt NPs anchor sites was fabricated by sp-N doping and γ-ray irradiation, which reduced the oxygen penetration barrier of original GY, exposed more active sites, shortened ion migration path and accelerated mass transfer, thus improving the ORR performance. The ORR activity of Pt/N50 -GY catalyst is superior to that of the commercial Pt/C and even more outstanding when compared with the mostly reported graphdiyne related and noble meal catalysts under lower catalyst loading. Additionally, the Pt/N50 -GY catalyst showed superior stability to the commercial Pt/C. Our work breaks the bottleneck that GY can not be applied to ORR, and provides a breakthrough way for the application of GY in ORR. Graphical abstract: Image, graphical abstract